A modern look at the methods of radiation diagnosis of osteoporosis - K. M. Vel'ma; E. A. Kalashnikova; Yu. V. Dovgyallo (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Osteoporosis, according to the World Health Organization, ranks fourth among the causes of death and disability after cardiovascular, oncological diseases and diabetes mellitus. Among residents of Russia over the age of 50, osteoporosis occurs in about one in three women and one in four men. This pathology has a high social significance, since it often causes a high level of disability of the adult population. From the point of view of reducing the incidence of mortality and disability of the able-bodied population from osteoporosis, the problem of its prevention and early diagnosis, including using radiation research methods, is paramount. Information on this issue is quite scattered today, requires systematization and generalization. The study and analysis of the available literature on the possibilities of radiation diagnosis of osteoporotic changes were carried out. Summarizing the available information on the radiation diagnosis of osteoporosis, we should talk about the need to introduce a preclinical examination for this pathology, since there is data on the results of opportunistic screening in some groups of patients. The vast majority of such cases are asymptomatic, which once again confirms the need for a preventive approach to this problem. Taking into account the variety of existing methods for diagnosing osteoporosis in the early stages, the most reliable, with some of its disadvantages (the presence of radiation exposure, the high cost of equipment), are still dual-energy X-ray densitometry and quantitative computed tomography, the analogue of which, with limited resources to provide equipment for medical institutions, is ultrasound densitometry.